Effects of flooding and redox conditions on solute diffusion in soil - Kirk, G.J.D.; Solivas, J.L.; Alberto, M.C. (Wiley, 2003)
Rates of solute diffusion fundamentally affect the properties of flooded soils, but the effects of flooding on solute diffusion have not previously been studied in detail. Four soils with widely differing chemical and physical properties were packed to a range of bulk densities, flooded for varying times, and the self‐diffusion of chloride through the soils measured. Diffusion impedance factors were derived from the results. In each soil the impedance factor decreased linearly with increase in bulk density, and between soils impedance factors increased with increasing clay content. The impedance factor decreased by up to 20% during the first 3–6 weeks following flooding, but with prolonged flooding it increased to at least its initial value. Concomitantly the cation exchange capacities of the soils increased by between 30 and 100%, there was reductive dissolution of soil iron, probably both structural iron in soil clays and iron oxyhydroxide coatings on clay surfaces, and subsequently there was re‐precipitation of ferrous iron, probably as mixed carbonates and hydroxides. The decreases in diffusion impedance factors were consistent with the increases in cation exchange capacity and changes in soil iron, and the subsequent increases were consistent with re‐crystallization of mixed ferrous–ferric compounds. We conclude that the effects of changes in redox on diffusion impedance will be important in some soils, although they are smaller than the effects of water content per se.